2008
DOI: 10.1007/s00285-008-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Invariant manifold reductions for Markovian ion channel dynamics

Abstract: We show that many Markov models of ion channel kinetics have globally attracting stable invariant manifolds, even when the Markov process is time dependent. The primary implication of this is that, since the dimension of the invariant manifold is often substantially smaller than the full master equation system, simulations of ion channel kinetics can be substantially simplified, with no approximation. We show that this applies to certain models of potassium channels, sodium channels, ryanodine receptors and IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 9 publications
2
54
0
Order By: Relevance
“…A comparison of the deterministic limits obtained for these models is provided in Appendix A and establishes an equivalence between these deterministic versions as soon as their initial conditions satisfy a combinatorial relationship. This question is further studied in [19], where the reduction of the law of jump Markov processes to invariant manifolds is investigated. We recall that every single ion channel process is independent within a subpopulation and between subpopulations.…”
Section: Application Of the Law Of Large Numbers To The Hodgkin-huxlementioning
confidence: 99%
“…A comparison of the deterministic limits obtained for these models is provided in Appendix A and establishes an equivalence between these deterministic versions as soon as their initial conditions satisfy a combinatorial relationship. This question is further studied in [19], where the reduction of the law of jump Markov processes to invariant manifolds is investigated. We recall that every single ion channel process is independent within a subpopulation and between subpopulations.…”
Section: Application Of the Law Of Large Numbers To The Hodgkin-huxlementioning
confidence: 99%
“…(4)- (7) can be simplified using the fact that it possesses two invariant manifolds 26 , so its dynamics can be reduced to a two dimensional dynamical system for two variables p and q, defined through P C = pq,…”
Section: Model and Approachmentioning
confidence: 99%
“…In this sense, both stochastic HH models can be considered as compatible with the original HH model as long as one is interested in the dynamics for theses special initial conditions. In Keener (2009), another result is obtained in a slightly different setting: assuming the transition coefficients to be only function of time, and forgetting V, it is shown that the corresponding invariant manifold is globally attracting under eigenvalues conditions.…”
Section: Comparison Between Two-state and Multistate Gating Schemesmentioning
confidence: 95%